Wild edible plants of the Central Mountains in Argentina. Comparing subregions to understand the complexity of local botanical knowledge - Saur Palmieri, Valentina (2022)
This work evaluates similarities and differences in the processing and consumption of wild flora in three subregions of Central Argentina. It aims to both deepen the knowledge of present local food culture and to contribute to the interpretation of the archaeobotanical data previously generated in the area. Open and semi-structured interviews were conducted in each subregion and the cultural importance index was calculated for each mentioned plant. A total of 45 species and 24 practices were listed and, while 42% of the taxa were common to the subregions, 33% of the species (e.g., Ximenia americana in the north) and 25% of the practices (e.g., “milanesa” in the west) were mentioned exclusively in one of them. These particularities were attributed to both ecological (i.e. plant availability) and socio-cultural factors (i.e. presence of neo-rural settlers). Our results enhanced our understanding of the local botanical knowledge of the entire mountain area, increasing the understanding of the region as a biocultural system and contributing to the conservation of the area. Moreover, the comparison between the taxa mentioned in the present and those listed in previous archaeobotanical studies in the area, showed that 78% of the wild taxa recovered from archaeological sites are mentioned in the present (e.g., Lithraea molleoides). Consequently, the present results about food processing are a basis for future studies of the human-plant relationship in the central mountains of Argentina over time.